Ultimate bearing capacity of peat treated with cement columns in physical model - Youventharan, Duraisamy; S. M., Arif; Rokiah, Othman (2019)
Peat is classified as very soft and problematic soil due to its natural behaviour of high compressibility, low in shear strength and with high natural water content. Cement column method is commonly used to stabilise the soil by improving the engineering properties. This research aimed to study the unconfined compressive shear strength and the ultimate vertical bearing capacity of stabilized tropical peat of East Coast of Peninsular Malaysia. A group of cement columns were tested in a series of physical model testing. To study the strength behaviour of peat with or without the cement stabilization, physical models were prepared with different variables such as; the number of cement column, proportion of binders (Ordinary Portland Cement-OPC) and the pozzolanic materials (Palm Oil Fuel Ash-POFA). In this research, a total of 9 physical models testing of peat soil including one without the stabilized cement column were conducted. A group of 4 and 6 cement columns with 25 mm diameter and 200mm in length each was installed. Samples were cured for 28 days as soon as the mixing of cement columns completed. After curing, a series of axial loads were applied uniformly on the pre-fabricated steel plate footing from the top of the cement column in order to study the ultimate bearing capacity of the stabilised soil. The change in strength of the soil was evaluated using Unconfined Compressive Strength (UCS) test. Based on the results, the highest ultimate bearing capacity was recorded in Model 6 with 6 cement columns with area improvement ratio of 18.83 %. The sample with 300kg/m3 of OPC has the highest UCS value of 106.88kPa. Hence, the cement columns mixed with binder and pozzolanic improved the strength and the ultimate bearing capacity of the peat soil.